Apoyo a la secretaría de infraestructura en la revisión y seguimiento de proyectos en Tibasosa, Boyacá (2023)
The text below serves as an information article in the practice modality in the Civil Engineering career of the Antonio Nariño University, with the purpose of carrying out the internship at the Infrastructure Secretariat of the municipality of Tibasosa, Boyacá, with the purpose. that the student provides support in the control of infrastructure projects and administrative work attributed through the resolution established by the entity and the university, carrying out activities such as budgeting, monitoring and site visits, writing documents. technicians, supervision of construction personnel and administrative work, such as the preparation of supervision reports and projection of construction monitoring minutes, as well as actively participating in projects and program plans of the entity developed through a mixed methodology supported by the fixed needs. The internship allows students to empirically verify the veracity and applicability of the theoretical content that is part of the training process. The relevance of the degree work in the institutional practice category is based on the importance of providing the knowledge acquired in the theoretical-practical field of all technical support activities that involve the review and execution of projects during the preparation time. at the students' university, as well as the aim of acquiring new knowledge, the result of practical exposure to construction processes and construction supervision.